An efficient scheme for secure data transmission in wireless sensor networks - Pathan, Al-Sakib Khan; Hong, Choong Seon (2007)
In this paper, we propose an efficient security scheme for wireless sensor networks which provides good level of confidentiality and authenticity of the data that are transmitted from the sensors to the base station. We use one-way hash chain and pre-stored shared secret keys for ensuring the data transmission security in the network. In our scheme, we first create a tree structure in the network and then use it for authenticated and encrypted data delivery. To introduce data freshness, our scheme includes an optional key refreshment mechanism which could be applied depending upon the requirement or the application at hand. We present a brief analysis along with the detailed description of our scheme.